Identification of a novel HLA‐A allele, A*11:209 by sequence‐based high‐resolution typing in an HIV‐infected individual. (8th April 2016) - Ou, G.; Wang, J.; Ji, X.; Chen, Q.; Liu, Z.
Abstract : The novel allele A*11:209 shows three nucleotides difference from A*11:27 in exon 3.